2014
DOI: 10.1073/pnas.1410569111
|View full text |Cite
|
Sign up to set email alerts
|

Protein−DNA binding in the absence of specific base-pair recognition

Abstract: Until now, it has been reasonably assumed that specific base-pair recognition is the only mechanism controlling the specificity of transcription factor (TF)−DNA binding. Contrary to this assumption, here we show that nonspecific DNA sequences possessing certain repeat symmetries, when present outside of specific TF binding sites (TFBSs), statistically control TF−DNA binding preferences. We used highthroughput protein−DNA binding assays to measure the binding levels and free energies of binding for several huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
134
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 42 publications
5
134
1
1
Order By: Relevance
“…We found that TF sequence preferences reach far beyond the core motifs and their direct flanks, which were previously shown to contribute to TF binding preferences (Gordân et al 2013;Afek et al 2014;Levo et al 2015). An intriguing question is how the protein can identify the unique environment so far beyond its binding site.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…We found that TF sequence preferences reach far beyond the core motifs and their direct flanks, which were previously shown to contribute to TF binding preferences (Gordân et al 2013;Afek et al 2014;Levo et al 2015). An intriguing question is how the protein can identify the unique environment so far beyond its binding site.…”
Section: Discussionmentioning
confidence: 54%
“…However, selective binding of motifs by TFs has also been observed in a variety of in vitro experiments (Noyes et al 2008;Badis et al 2009;Berger and Bulyk 2009;Zhao et al 2009;Slattery et al 2011;Enuameh et al 2013;Gordân et al 2013;Jolma et al 2013;Afek et al 2014;Weirauch et al 2014;Abe et al 2015;Levo et al 2015). These in vitro studies show that TFs can bind to different sequences containing a similar motif with a large range of different affinities, which suggests that TF-DNA binding specificity is influenced by the DNA context surrounding the motif.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…DNA sequence and shape preferences at flanking regions of core motifs play important roles in achieving binding specificity for TFs from certain protein families, both in vitro (Gordân et al 2013;Afek et al 2014) and in vivo . However, these DNA properties alone are insufficient to explain the different in vivo TF binding preferences observed across distinct cell types (The ENCODE Project Consortium.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados de estudos nesta linha podem impactar a compreensão dos princípios moleculares biofísicos de regulação da transcrição e melhorar significativamente a nossa capacidade de prever como as variações nas sequências de ADN, tais como mutações ou polimorfismos e concentrações de proteína, influenciam programas de expressão gênica em células vivas [1]. Apesar de ser largamente aceito, a forma geral da difusão facilitada, a princípio, apresentaria um problema conhecido como paradoxo velocidade-estabilidade.…”
unclassified